Building the right foundation - Ishak, Mohamed Mustafa (The Star, 2014)
THE heirs of the nation's future are its youth. This has pressed the leaders of Malaysia to place emphasis on the nurturing of the country's youth to secure a favourable future for the nation as a whole. The nation is earnest in moving forward, exemplified through the devising of strategies for its transformation.